From intimacy to reflection: about the ethnographic documentary Xennials: Sobre el documental etnográfico Xennials - Chávez López, Paula (2022)
In Peru, half of the population are women and have a longer life expectancy. They are presented as those who live for others, at all ages, and at all socio-economic levels, therefore it is affirmed that they live in ‘time poverty’. Almost no free time or for personal activities, dedicated to delivering their physical and mental potential, both in the private and public spheres and in a context where patriarchy reigns and the rates of gender violence are among the highest in the region. This article aims to understand how, currently, Lima women of the micro generation Xennials, belonging to a very broad middle class, perceive and experience their present time and, retrospectively, the past time. With main emphasis on the methodology used: a documentary ethnography as field work, applying in-depth interviews, life stories, timelines, as well as personal video diaries narrated by the protagonists that enrich their own portraits. Although the results are based on the subjectivities of the subjects, a reflective dimension is also shown, with a view to self-recognition of their identities in today's society.